1642e Project-based training as a tool to tackle occupational health challenges in developing countries. (24th April 2018) - Radon, K; Kurtz, L; Carvalho, D; Encina, V; van Dijk, F; Meneses, C; Garrido, MA; Bauleo, MF; Briceño, L; Herrera, R; Parra, M
Abstract : Introduction: To know the prevalence of exposures and diseases at workplaces is crucial for the development of intervention strategies and healthcare planning. However, in many low and middle-income countries (LMIC) research is no priority. One reason is a lack of experts able to carry out sound epidemiological research at workplaces. One way of preparing such experts is through project-based training. We therefore implemented a project as training method in our blended learning Master in International Occupational Safety and Health (OSH). Methods: Students start by identifying their research interest based on existing worker's health problems. They develop a study protocol to assess working conditions and health at a self-selected workplace. After ethics approval, they carry out the project during the 2nd term of the program. In term 3, they learn to analyse and interpret data and develop a teaching intervention. In the final term, students write the master thesis in form of a scientific paper. Throughout the process, they are accompanied by a tutor. Results: Since its beginning in 2012, the number of participants in the program is stable with 10–12 students/year. All of them are OSH experts with at least 2 years of experience in the field coming from eight Latin American countries. Students evaluate the project-based learning approach as positive. Of the 43 graduating students, 9 research papers were published in journals. More than half of the graduates teach students at local universities and thereby act as multipliers. Few continue to carry out research mainly due to lack of priority in their home countries. Discussion: The project-based learning approach contributes to occupational health research in Latin America. The concept might be promising also for other LMIC. However, due to the individual tutoring the program is cost intensive, publication of the results challenging and work opportunities for researchers limited.